THE IMPACT OF THE BLENDED LEARNING MODEL ON ENGLISH LANGUAGE EDUCATION IN UZBEKISTAN - Khasanova Maftuna Ikhtiyorovna (Web of Journals Publishing, 2025)
The integration of the blended learning model in English language education has gained significant attention in Uzbekistan, particularly in response to the growing demand for digitalization in education. This paper examines the impact of blended learning on English language acquisition, focusing on its advantages, challenges, and effectiveness in the Uzbek educational context. The study highlights how blended learning combines traditional face-to-face instruction with digital resources, enhancing student engagement, motivation, and language proficiency.
Keywords: Blended learning, English language education, digital learning, Uzbekistan, language proficiency, online education, teacher training, student engagement.